Applications of Shape Memory Alloys for Neurology and Neuromuscular Rehabilitation - Simone Pittaccio; Lorenzo Garavaglia; Carlo Ceriotti; Francesca Passaretti (Journal of Functional Biomaterials, 2015)
Shape memory alloys (SMAs) are a very promising class of metallic materials that display interesting nonlinear properties, such as pseudoelasticity (PE), shape memory effect (SME) and damping capacity, due to high mechanical hysteresis and internal friction. Our group has applied SMA in the field of neuromuscular rehabilitation, designing some new devices based on the mentioned SMA properties: in particular, a new type of orthosis for spastic limb repositioning, which allows residual voluntary movement of the impaired limb and has no predetermined final target position, but follows and supports muscular elongation in a dynamic and compliant way. Considering patients in the sub-acute phase after a neurological lesion, and possibly bedridden, the paper presents a mobiliser for the ankle joint, which is designed exploiting the SME to provide passive exercise to the paretic lower limb. Two different SMA-based applications in the field of neuroscience are then presented, a guide and a limb mobiliser specially designed to be compatible with diagnostic instrumentations that impose rigid constraints in terms of electromagnetic compatibility and noise distortion. Finally, the paper discusses possible uses of these materials in the treatment of movement disorders, such as dystonia or hyperkinesia, where their dynamic characteristics can be advantageous.